PEMUSNAHAN BARANG ILEGAL DI ACEH DALAM PERSPEKTIF UNDANG-UNDANG NO. 17 TAHUN 2006 DAN HUKUM ISLAM - Cut Elfida (Universitas Islam Negeri Ar-Raniry, 2016)
Today the entrance and exit of illegal goods in a country is often the case, including Indonesia. This is contrary to the customs law No. 17 of 2006, as amendments to the law No. 10 of 1995. If the imported goods do not meet the requisite as stipulated in the customs law, the goods are said as illegal goods. Genesis in the field to the treatment of illegal goods destroyed by burning, or by enterning in the warehouse with a long time which causes demage to the goods, and then destroyed. Problems and purposes of this study is to know how the market effect that occurs when the entry of illegal goods in a market's mechanism, and to know the benefit of the concept being taught in Islam to the treatment of illegal goods are allowed substance. In this study the authors used a case study method with a qualitative research approach. The result showed that there was no market effects occur very losers against the entry of illegal goods, because not so much to get in or not completed recorded by authorities. Therefore, by looking at the fact that the authorities to the treatment of illegal goods such as illegal onions and sugar to put in a warehouse with a long time and then destroyed, or directly burn it, so that's way is the redundant, because there are still other ways that are benefit of it, such as submitting to Baitul Mal if the owner did not take care. So, Baitul Mal became a guardian on illegal goods and the results are given to requiring people's as contained in the Qanun No. 10 of 2007 on the Baitul Mal and fatwa's MPU (Ulama's Consultative Assembly), to sell at a cheaper price than the market price if the buyers are less able or it's free to them, or with the market price if the buyers are general public.